Nonlinear ergodic theorems for a semitopological semigroup of non-Lipschitzian mappings without convexity - G. Li; J. K. Kim (Abstract and Applied Analysis)
Let G be a semitopological semigroup, C a nonempty subset of a real Hilbert space H, and ℑ={Tt:t∈G} a representation of G as asymptotically nonexpansive type mappings of C into itself. Let L(x)={z∈H:infs∈Gsupt∈G‖Tts x−z‖=inft∈G‖Tt x−z‖} for each x∈C and L(ℑ)=∩x∈C L(x). In this paper, we prove that ∩s∈Gconv¯{Tts x:t∈G}∩L(ℑ) is nonempty for each x∈C if and only if there exists a unique nonexpansive retraction P of C into L(ℑ) such that PTs=P for all s∈G and P(x)∈conv¯{Ts x:s∈G} for every x∈C. Moreover, we prove the ergodic convergence theorem for a semitopological semigroup of non-Lipschitzian mappings without convexity.